Finite Element Simulation Of Laser Welding Of Tailor Welded Blank On Different Material - Chu, Yin Yeng (Universiti Sains Malaysia, 2017)
Automotive companies now prefer forming the parts from tailor-welded blanks (TWB) for lighter weight parts. The TWB consists of more than two sheets with different material mainly due to advantages in reducing weight. TWB is typically welded using laser since it produces a narrow weld bead, lower distortion, residual stress and strain. Many studies have presented a wide range of information about the weldability and failure patterns of TWB. However, accurate prediction of formability of blank after welding such as springback remains elusive. In this study, a three-dimensional finite element analysis (FEA) was carried out to perform the laser welding using non-linear heat transfer analysis with ANSYS workbench package. This project focuses on the laser welding simulation and the springback effect observed on the TWB. It found that the affected temperature range of laser welding is depends on the laser power. The appropriate welding temperature range based on the material properties resulted with conduction mode laser power is simulated in this paper. Furthermore, springback effect of blank was measured through longitudinal V-bending process. The plasticity deformation and springback of the blank was fully obtained and studied through static structural analysis used in ANSYS workbench.